MODEL PERENCANAAN STRATEGIS SISTEM INFORMASI (STUDI KASUS PADA PEMERINAH DAERAH KEPULAUAN ANAMBAS) - Aditya Dwi Bachtiar; Ravina Arsta Tamara; Roy Rafi Donissafaat (Jurnal Aplikasi Teknologi Informasi dan Manajemen (JATIM), 2020)
The use of IT / SI is an organization's needs in running its business and services. IT / SI is mostly done by the Government in carrying out its activities and services taken from others efficiently, effectively, and approved to support good and clean governance. KPPKB (Office of Empowerment of Women and Family Planning in Anambas Islands Regency) has also used IT / SI in carrying out its duties and services. The use of IT / SI in the Anambas Islands Regency KPPKB Office has not been carried out completely and many conventional activities have not been able to support optimal achievement of targets and performance. To obtain organizational goals, IT / SI strategies are needed in common with business strategies. This article discuss the steps in the analysis of information systems strategic planning at the Office of the KPPKB (Empowering Women and Family Planning) in the Anambas Islands Regency using the work of Ward and Peppard. The analysis tools used are PEST, CSF, SWOT, Value Chain and McFarlan Strategic Grid. The final results are expected to help the Anambas Islands District Women's Empowerment and Family Planning Office to be better in the system planning.